PENERJEMAHAN MAJAS DALAM LIMA PUISI KARYA PENYAIR AMERIKA - PRESSANTI, DESI ARI (Kementerian Sekretariat Negara Republik Indonesia, 2015)
This article analyzes the quality of language usage utilized by writers/translators of bilingual handbooks for Physics, Economics and History that are used in Indonesian Junior High Schools. Ten translation version texts produced by the writers/translators are collected to be the objects of the research to be analysed for their quality of grammatical construction as well as lexical selection. The assessment of three raters are also obtained as the data for the accuracy and the acceptability of the texts, whereas the assessment of the users of the books are collected to verify the readibility of the texts. Although the results still show several weaknesses in grammatical construction and lexical choices, the writers/translators generally produced good quality translations. This is evidenced by the accuracy, acceptability, and readability of the texts that are of high rate. Among the lessons that can be derived from this analysis is that writers/ translators are recommended to keep upgrading their skills in the use of the English grammar and also in the choice of English vocabulary in order to attain excellence in their profession. Keywords: bilingual handbook, translation, grammar usage, lexical choice, translation quality